Tinjauan Normatif Kewenangan Penuntutan oleh KPK Atas Tindak Pidana Pencucian Uang - Pohan, Sarmadan (DOKTRINA: JOURNAL OF LAW, 2019)
Debate over the issue of the authority of the corruption eradication commission in conducting investigations, investigations and investigators. The purpose of this study is to examine the legal basis for the authority to prosecute KPK for money laundering and the position of the authority to prosecute corruption eradication commissions for money laundering crimes in the future. This research method is normative, in which research of document studies using a variety of secondary data. The results obtained from this study are that the Article 6 of Law Number 30 of 2002 that the KPK only has authority in conducting investigations, investigations and prosecutions of money laundering crimes. In IusConstitutim or what applies in a regulation or better known as the law, the Corruption Eradication Commission does not have the authority to prosecute money laundering, different empirically different from seeing what happens in society that the KPK is deemed necessary to prosecute a laundering crime in TPPU is a double-track criminality in which there is an original and advanced crime, if the money laundering is a further criminal act of corruption as an original criminal act empirically then the Eradication Commission Corruption continues to prosecute because it still have a rights.